2020
DOI: 10.1101/2020.07.23.218446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic Effects of the DRD2/3 Antagonist ONC201 and Radiation in Glioblastoma

Abstract: BackgroundGlioblastoma (GBM) is the deadliest of all brain cancers in adults. The current standard-of-care is surgery followed by radiotherapy and temozolomide, leading to a median survival time of only 15 months. GBM are organized hierarchically with a small number of glioma-initiating cells, responsible for therapy resistance and tumor recurrence, suggesting that targeting glioma-initiating cells could improve treatment response. ONC201 is a first-in-class anti-tumor agent with clinical efficacy in some form… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Innovations in GBM treatment highlight the effectiveness of DRD2/3 antagonists combined with radiation therapy, and the role of D2 activation in tumor growth and stem‐cell‐like transitions 52,53 . Our study provides the first evidence of D2R expression increase in human GBM cell lines due to chronic morphine treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Innovations in GBM treatment highlight the effectiveness of DRD2/3 antagonists combined with radiation therapy, and the role of D2 activation in tumor growth and stem‐cell‐like transitions 52,53 . Our study provides the first evidence of D2R expression increase in human GBM cell lines due to chronic morphine treatment.…”
Section: Discussionmentioning
confidence: 73%
“…51 Innovations in GBM treatment highlight the effectiveness of DRD2/3 antagonists combined with radiation therapy, and the role of D2 activation in tumor growth and stem-cell-like transitions. 52,53 Our study provides the first evidence of D2R expression increase in human GBM cell lines due to chronic morphine treatment. Morphine derivatives, commonly used in GBM pain management, do not exacerbate tumorigenesis or radio-resistance in GBM cells, as indicated by studies on MTD.…”
Section: Exploring New Treatment Avenues: Focus On Cabergolinementioning
confidence: 73%
“…29 In mouse models, ONC201 crosses the blood-brain barrier, inhibiting GBM growth and increasing the median survival time when combined with radiotherapy. 29,64 To date, clinical trials using ONC201 have shown signs of efficacy in biomarker-defined recurrent GBM patients, 64,65 as well as in pediatric and adult H3 K27M-mutant glioma. [65][66][67] Noteworthy, ONC201 is also in Phase II clinical trials for AML, 68,69 breast cancer, 69,70 colorectal cancer, 69,71 lung cancer, 71 endometrial cancer, [69][70][71] and multiple myeloma.…”
Section: Drs In Glioblastoma (Gbm)mentioning
confidence: 99%
“…2,62 DRD2 silencing, 62 but also DRD4 silencing 32 or trifluoperazine treatment, 53 reduces the clonogenicity of GBM cells, an in vitro subrogate measurement of the CSC content. ONC201 reduces the self-renewal of glioblastoma CSCs in vitro 64 and inhibits the proliferation of CSCs in 3D neurospheres culture established from freshly isolated human glioblastoma tumors. 29 Similarly, the DRD4-selective antagonists L-741742 and PNU-96415E decrease GBM stem cell viability and block their clonogenicity but do not affect normal neural a 2C-AR: 7.4 # a 2B -AR: 7.2 # 5-HT 2C : 7.0 # 5-HT 1A : 6.9 (partial) 5-HT 2A : 6.9 # 5-HT 2B : 6.9 # a 2A -AR: 6.9 (partial) NSCLC 50 (continued) stem cells.…”
Section: Drs In Glioblastoma (Gbm)mentioning
confidence: 99%